Anthropometry, Physical Fitness and Coordination of Young Figure Skaters of Different Levels - Mostaert, M.; Deconinck, F.; Pion, J.; Lenoir, M. (International Journal of Sports Medicine, 2016)
The aim of the present study was to identify anthropometric, physical, coordinative and ice-skating specific characteristics that discriminate young elite ice skaters from non-elite skaters and their non-skating peers. 32 skaters aged 9–12 years old (11 elites and 21 non-elites) voluntarily participated in the study. They were submitted to 5 anthropometric, 7 physical, 3 coordination and 5 ice-skating specific tests. Reference values of a representative healthy non-skating sample were taken from the Flemish Sports Compass dataset. Figure skaters appeared to be predominantly average mature (93.8%), were lighter and leaner than the reference sample, and demonstrated better physical characteristics and motor coordination. There was no difference between the elite and non-elite group regarding maturity status and anthropometric or physical parameters. Still, elite skaters scored better than non-elites on the coordination tests jumping sideways and tended to do so on the moving sideways test. Profiles of figure skaters differ clearly from a reference population, while non-sport-specific motor coordination tests allow discrimination between elite and non-elite skaters. The relevance of these findings with respect to talent detection and identification in young ice skaters are discussed.
Keywords: figure skating; talent identification; talent detection